Comparison of Functional Outcomes of Endoscopic Lobectomy versus Open Lobectomy in Benign Thyroid Disease; A Randomized Controlled Trail - Warda Khalid, Muhammad Imran Khokhar, Syed Jawad Asad Gillani, Rohma Akhtar, Muhammad Khalid, Hafiz Muhammad Abdullah Tahir, Mirza Zeeshan Sikandar (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Thyroid nodules are nodules which commonly arise within an otherwise normal thyroid gland. A comprehensive history & physicals examination provides the foundations for decisions making in the managements of thyroids nodule. Endoscopic thyroidectomy is a newer technique and it is not accepted as a routine operation for thyroid diseases. With rising female gender, age, anemia & history of thyroid therapy, the possibility of thyroid nodules is greater. Objective: To compare the outcome of endoscopic lobectomy versus open lobectomy for benign diseases of thyroid gland Methodology: Randomized control trial was conducted in which after meeting the inclusion criteria 60 patients were participated in this study. Then patients were divided into two groups. One group is treated with endoscopic lobectomy technique and other with open lobectomy technique. During surgery, operative time was noted and then hospital stay was noted. Results: The’ patients average age was 28.68± 10.38 year, patients with endoscopic lobectomy procedures the mean surgery duration of patients was 101.60±24.16 minutes whereas among patients with open lobectomy surgical procedures the patients mean of surgery duration was 120.43±38.18 minutes (p-value=<0.05), similar finding observed in terms of hospital stay. Practical Implications: This will help in the early and prompt management of the thyroid swellings without causing any cosmetic effect and thus time saving and more efficient procedure would be endoscopic reresection of thyroid gland. Conclusion: The endoscopic lobectomy showed significantly better outcome than to open lobectomy for management of benign diseases of thyroid gland Keywords: Thyroid Gland, Benign, Endoscopy, Lobectomy, Pakistan